2016
DOI: 10.1007/s10902-016-9783-4
|View full text |Cite
|
Sign up to set email alerts
|

Brilliant: But What For? Meaning and Subjective Well-Being in the Lives of Intellectually Gifted and Academically High-Achieving Adults

Abstract: Not much is known today about relationships between giftedness and well-being, particular among adults. The present article examined if highly gifted people manage to live meaningful and happy lives in their adult years. Two aspects of giftedness were taken into account: intellectual giftedness, and academically high achievement. Representatives of both groups were compared with each other and a control group with regard to meaningfulness and subjective well-being, respectively. Furthermore, predictors for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 66 publications
(89 reference statements)
4
79
0
5
Order By: Relevance
“…Consistent with previous cross-sectional research (Phillips and Ferguson 2013;Pollet and Schnell 2017;Wong and Yeung 2017;Zessin et al 2015), the data revealed moderate to strong correlations between self-compassion, subjective well-being, and life meaning at both times of measurement. Furthermore, the results of the autoregressive model corroborated the assumption of construct stability.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Consistent with previous cross-sectional research (Phillips and Ferguson 2013;Pollet and Schnell 2017;Wong and Yeung 2017;Zessin et al 2015), the data revealed moderate to strong correlations between self-compassion, subjective well-being, and life meaning at both times of measurement. Furthermore, the results of the autoregressive model corroborated the assumption of construct stability.…”
Section: Discussionsupporting
confidence: 89%
“…A priori power analysis (G*Power; Faul et al 2007) revealed a required total n = 98 to determine at least a medium effect (f 2 = 0.15, α = 0.05, 1 − β = 0.80). Considering aforementioned findings (e.g., Pollet and Schnell 2017;Zessin et al 2015), we expected at least medium effects in regard to the associations between the three tested constructs.…”
Section: Methods Participantsmentioning
confidence: 83%
See 3 more Smart Citations